2016
DOI: 10.1186/s13033-016-0100-8
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge evaluation in dementia care networks: a mixed-methods analysis of knowledge evaluation strategies and the success of informing family caregivers about dementia support services

Abstract: BackgroundIn general, most people with dementia living in the community are served by family caregivers at home. A similar situation is found in Germany. One primary goal of dementia care networks is to provide information on support services available to these caregiving relatives of people with dementia via knowledge management. The evaluation of knowledge management tools and processes for dementia care networks is relevant to their performance in successfully achieving information goals. One goal of this p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…This allows DCNs to tailor interventions to dimensions that are important to caregivers at any point of time and to validly evaluate such interventions by specifically measuring these dimensions (Thyrian et al, 2016). For example, in a different line of analysis of the DemNet-D data, we found that caregivers who needed information on dementia support services were both successful at obtaining such information through their DCNs and more successful in this regard than non-DCN users (Heinrich et al, 2016). This finding is also reflected in our current analysis, where we found a significant reduction in caregiver burden in relation to the "Dealing with authorities, administrations" burden sub-scale.…”
Section: Discussionmentioning
confidence: 87%
“…This allows DCNs to tailor interventions to dimensions that are important to caregivers at any point of time and to validly evaluate such interventions by specifically measuring these dimensions (Thyrian et al, 2016). For example, in a different line of analysis of the DemNet-D data, we found that caregivers who needed information on dementia support services were both successful at obtaining such information through their DCNs and more successful in this regard than non-DCN users (Heinrich et al, 2016). This finding is also reflected in our current analysis, where we found a significant reduction in caregiver burden in relation to the "Dealing with authorities, administrations" burden sub-scale.…”
Section: Discussionmentioning
confidence: 87%
“…Within these interviews, data about successful financing, governance, and knowledge management processes in DCNs were extracted. 6,8,11,12 The analyzed qualitative data were the basis for the website content because the website aimed to inform DCN stakeholders and other interested persons about processes who bring DCNs to work and their optimization. The website development was performed by two interdisciplinary teams.…”
Section: Methodsmentioning
confidence: 99%
“…This is why, in many cases, one DCN knows little about the structures and processes of other DCNs, including facilitators or inhibitors for initiating different network processes (e.g., knowledge management/financing/governance) or reaching specific network aims. 6,8,11,12 Therefore, another aim of the DemNet-D study was to achieve the goal of disseminating practice-friendly information about DCNs to other interested DCN and health-care stakeholders in the field of dementia care who want to optimize existing networks or build new DCNs based on the DemNet-D research findings. Like key persons in DCNs, these persons may be home care staff, nurses, and physiotherapists as well as general practitioners and other health-care stakeholders who might be interested or involved in the field of dementia support.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, caregivers should find some strategies to alleviate their own physical and mental health. Previous qualitative studies examined the following values of caregivers and PwD: family and social relationships, safety and physical health, emotional well-being, support for care needs and daily functioning, related services, medical care, support networks and meaningful activities (Heinrich, Uribe, Wübbeler, Hoffmann, & Roes, 2016;Macrae, 2010;Phinney, Chaudhury, & O'Connor, 2007). Furthermore, the positive and negative aspects of caregiving are of the same continuum-they could influence caregiver well-being and satisfaction with life (Lethin et al, 2017).…”
Section: Introductionmentioning
confidence: 99%